THE APPLICATION OF BASIC PRINCIPLES OF ONLINE LEARNING THROUGH GOOGLE SUITE FOR EDUCATION DURING COVID19 OUTBREAK - Afrianto Daud; Mirza Hardian (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
As education worldwide is now switching massively to a virtual class during the pandemic, a teacher needs to understand online learning's philosophy and principles to make sure the class can run effectively. This paper aims to examine the current situation of online learning after the Covid19 outbreak and discusses the implementation of basic concepts of online learningby utilizing Google Suite products such as Google Classroom, Google Meet, Google Doc, and Google FormsAdopting the idea of a library research approach, data of this study were taken entirely from the secondary data by first searching some relevant resources in the area of online learning. The primary database used for searching the relevant resources is the e-resources of the Indonesian national library. The databases here have been connected to various reputable international databases such as ProQuest, EbscoHost, SAGE, Sciencedirect, Taylor & Francis, and many more. The data include those taken from e-books, journal papers, and scholarly articles. Taking data from these reputable resources is necessary to enhance the quality of the data collected. Among the basic concepts for effective online learning are that teachers or lecturers need to ensure the following principles considered when designing and implementing online learning: student-centered learning activities leading to self-regulated learning, interactivity, and strive for presence (in social, cognitive, and teaching aspects during learning).